(3GdJfHjg Ydi GdeYGfi hGdCSHGH GdJi ChLHJ GdNdGa Hjf GdeSdejfs - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eSHZ GdfYe , heShZ GdbSe hEfi deG QCjJ GdfGS bO CaQWhG ai GdJCdja hdjS ZQVi ef cJGHi gPG Cf JYde ai GdCSHGH GdJi ChLHJ GdNdGa GdCYXe s
(3BNQgG (B:s
(3GdHGH GdKGef ai GdNdGa GdYGQV ef bHd GdEHGMI hCfG CSJZaQ ef gPG Ef cGf YQV hCSCdg YhfkG Ydi eG Hg JYHO haQV hUdi Gddg Ydjg hYdi Bdg hSde CaVd GdJSdje ced HMeO Gddg hMSf Yhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B488s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GNJdGa GdabgGAs